Sea Salts Contamination Pattern on High Voltage Insulators In Littoral Region of Peninsular Malaysia - Ahmad, Ahmad S.; Ahmad, Hussein; Salam, Md. Abdus (1999)
This paper describes series results of experiments conducted at Paka Thermal Power Station, which is located near the East Coast of Peninsular Malaysia. More than 12 samples of typical cap-and-pin glass insulators that are commonly installed on electrical power transmission lines are used in the experimentation. Three types of insulator topology are employed, single units, suspension-type and tension-type. These un-energized insulators are allowed to be exposed to 3-4 months duration of sea salts contamination. Equivalent salt deposit density (ESDD) measurement is conducted to measure insulator's contamination level. It was found that salt accumulation on suspension type insulator is much heavier than the tension type. Also the direction of inward coming winds has some influence on the salt deposition to the insulator surfaces. Experiments showed that ESDD increases linearly with an increase in time of exposure. This work will help in the establishment of maintenance policies especially in the months of monsoon when generally many utilities thought that during these months maintenance of insulators is not necessary